Early profiles of clinical evolution after intravenous thrombolysis in an unselected stroke population. Issue 3 (22nd October 2009) - Delgado, M G; Michel, P; Naves, M; Maeder, P; Reichhart, M; Wintermark, M; Bogousslavsky, J
Abstract : Background: Intravenous recombinant tissular plasminogen activator (rt-PA) is the only approved pharmacological treatment for acute ischaemic stroke. The authors aimed to analyse potential causes of the variable effect on early course and late outcome. Methods and results: 136 patients (42% women, 58% men) treated with intravenous rt-PA within 3 h of stroke onset in an acute stroke unit over a 3-year period, were included. Early clinical profiles of evolution at 48 h were divided into clinical improvement (CI) (decrease >4 points in the National Institute of Health Stroke Scale (NIHSS)); clinical worsening (CW) (increase >4 points NIHSS); clinical worsening after initial improvement (CWFI) (variations of >4 points in the NIHSS). Patients with clinical stability (no NIHSS modification or <4 points) were excluded. The patients showed in 66.9% CI, 13.2% CW 8.1 % CWFI and 11.8% remained stable. Female sex, no hyperlipaemia and peripheral arterial disease were associated with CW. Male sex and smoking were associated with CI. Absence of arterial occlusion on admission (28.4%) and arterial recanalisation at 24 h were associated with CI. Main causes of clinical deterioration included symptomatic intracranial haemorrhage (sICH), persistent occlusion and cerebral oedema. 23.5% developed ICH, 6.6% of which had sICH. At 3 months, 15.5% had died. Mortality was increased in CW, mainly related to sICH and cerebral oedema. The outcome of CWFI was intermediate between CW and CI. Conclusions: Early clinical profiles of evolution in thrombolysed patients vary considerably. Even with CI, it is critical to maintain vessel permeability to avoid subsequent CW.